2023
DOI: 10.1007/s00401-023-02654-1
|View full text |Cite
|
Sign up to set email alerts
|

“De novo replication repair deficient glioblastoma, IDH-wildtype” is a distinct glioblastoma subtype in adults that may benefit from immune checkpoint blockade

Sara Hadad,
Rohit Gupta,
Nancy Ann Oberheim Bush
et al.

Abstract: Glioblastoma is a clinically and molecularly heterogeneous disease, and new predictive biomarkers are needed to identify those patients most likely to respond to specific treatments. Through prospective genomic profiling of 459 consecutive primary treatment-naïve IDH-wildtype glioblastomas in adults, we identified a unique subgroup (2%, 9/459) defined by somatic hypermutation and DNA replication repair deficiency due to biallelic inactivation of a canonical mismatch repair gene. The deleterious mutations in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Accurate identification of at-risk populations will assist in developing early disease surveillance and intervention programs for detecting precancerous lesions or early-stage tumors. Studies have shown that the early stages of LS-related tumors exhibit greater sensitivity to immune checkpoint inhibitors ( 26 ), and patients with GBMs resulting from underlying LS may benefit from these medicines like pembrolizumab ( 27 ). Therefore, keenly identifying patients with suspected LS, confirming the diagnosis with genetic testing, and subsequently developing individualized treatment plans for them are of great significance for improving patients’ quality of life in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate identification of at-risk populations will assist in developing early disease surveillance and intervention programs for detecting precancerous lesions or early-stage tumors. Studies have shown that the early stages of LS-related tumors exhibit greater sensitivity to immune checkpoint inhibitors ( 26 ), and patients with GBMs resulting from underlying LS may benefit from these medicines like pembrolizumab ( 27 ). Therefore, keenly identifying patients with suspected LS, confirming the diagnosis with genetic testing, and subsequently developing individualized treatment plans for them are of great significance for improving patients’ quality of life in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these tumors were epigenetically distinct from IDH-mutant astrocytomas, with reduced global methylation levels, and were distinguishable with methylation profiling from secondary MMR-deficient tumors, which tended to match better with their MMR-retained IDH-mutant astrocytoma counterparts [ 59 , 200 ]. This may also be true of IDH-wild-type glioblastomas [ 87 ], suggesting that there may be fundamental differences in the biology of tumors with acquired and germline MMR mutations.…”
Section: Mismatch Repair (Mmr) Protein Defects and Microsatellite Ins...mentioning
confidence: 99%
“…MMR mutations also increase the number of neoantigens (mutant proteins potentially viewed as novel by the immune system) [ 15 , 109 , 112 , 135 ], with some data suggesting that as many as 42% of nonsynonymous mutations in exon regions may result in neoantigen formation [ 17 ]. This property makes immune checkpoint inhibitor therapy an attractive adjuvant treatment option for these tumors [ 24 , 47 , 53 , 83 , 87 , 93 , 101 , 112 , 131 , 180 , 182 , 209 ], although not all hypermutant cancers respond [ 112 , 143 , 180 , 209 ]. Other studies have suggested that immune therapy may only remove MMR-mutant subclones [ 140 , 180 , 220 ], so this therapy may be most effective in patients with germline mutations as the MMR mutations are more uniform in these cases [ 24 , 200 ].…”
Section: Mismatch Repair (Mmr) Protein Defects and Microsatellite Ins...mentioning
confidence: 99%